Centers of excellence or excellence networks: The surgical challenge and quality issues in rare cancers. Issue 1 (January 2019) - Sandrucci, S.; Naredi, P.; Bonvalot, S.
Abstract: There are several suggestions that centralization of care improves outcome for rare cancers, particularly when optimal treatment requires complex surgery or high-technology radiotherapy equipment. Diagnosis and treatment in reference centers are expected to be more accurate because they benefit from large numbers of cases discussed in a multidisciplinary tumor board with a well-run pathway. However, centralization is sometimes moderately perceived by oncologists as a solution to be endorsed for rare cancer patients; disadvantages of centralization are the need for patients to move and the risk of a longer waiting list, with discomfort and possible negative effects on outcome. It is difficult to find single experts on rare cancers: all the more it will be difficult to find a multidisciplinary panel of experts, and the role of the surgeon is to be a functional part of it. On the other side, from a surgical point of view, the quality of the initial management of many rare cancers directly impacts the final outcome; surgery of rare cancers may not necessarily be more demanding than the average from a technical point of view, but the lack of cultural knowledge about the disease can well lead to inappropriateness even in the lack of major technical challenges. Care for rare cancer patients must be organized in pathways that cover the patient's journey from their point of view rather than that of the healthcare system, and pathways must follow the best evidence on diagnosis, treatment and follow-up.